Gender-specific association between uric acid level and chronic kidney disease in the elderly health checkup population in China. (1st January 2019) - Yang, Yanlang; Zhou, Wei; Wang, YuWei; Zhou, Ru
Abstract: Objective : To evaluate the association between serum uric acid (SUA) levels with CKD in elderly health checkup population and explore the gender difference. Methods: A total of 4242 subjects were included in the cross-sectional study. All of the subjects participated in the annual checkup between June 2016 and June 2017. Chronic kidney disease (CKD) was defined by estimated glomerular filtration rate (eGFR) <60 ml/min per 1.73 m 2 . We examined the association between SUA levels and CKD. Multivariate binary logistic regression analysis was used to estimate odds ratios (ORs) and 95% confidence intervals (95%CIs) by comparing association between the SUA level and CKD. The models were adjusted for age, gender, body mass index (BMI), hypertension, diabetes, triglyceride and high-density lipoprotein cholesterol (HDL-C). Result: The prevalence of hyperuricemia was 22.2%, and it was significantly higher in male than in female (25.2% vs. 17%, p < .001). The prevalence of hyperuricemia increased with age, especially in the female. The prevalence of CKD was 27.8% in male and 20.2% in female ( p < .001). Compared with the SUA first quartile, the multivariate-adjusted odds for CKD of fourth quartiles were 6.05 (95%CI: 4.32–8.49) in male and 8.21(95%CI: 5.37–12.54) in female. Conclusion: Our finding showed gender-specific differences in the association between high SUA and an increased risk of CKD in the elderly population. The association of SUA and CKD was independent of other potential confounding factors including age, glucose, hypertension, HDL, TG and BMI.